Governance Capacity of Local Government in Empowering Small and Medium Enterprises in Indonesia - Maria R. Harni Triastuti (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Local governments play a strategic role in promoting regional economy. However, case studies on economic empowerment of the people indicate a less optimally stipulated target of the government in terms of financial capacity, human resources and program effectiveness. Such a condition might be due to the lack of governance capacity of the local government in empowering small and medium enterprises (SMEs). This paper discusses the role of local governments in supporting local businesses and their governance capacity required to play such a role. A case study is provided of four local governments in Indonesia. We find that both inside-out and outside-in factors influence local governance capacity. By inside-out factors we mean the governments’s self-disclosure in their cooperation with stakeholders to optimize the use of resources and their public accountability. The outside-in factors includes the challenges and barriers to the administrative environment that affects governance capacity.